Criteria to Support the Transition Towards Circular Supply Chains – Integrating Legal, Practical and Academic Perspectives - Pelzeter, Andrea; Bustamante, Silke; Martinovic, Martina; Zimmermann, Roxana (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Circular Economy (CE) has emerged as a trend in both practical and academic discourse and has recently been adopted into core EU sustainability legislation such as the Eco-Design Directive. Redesigning supply chains to incorporate principles of circularity bears the potential to enhance sustainability performance. However, to date, holistic, inclusive, and versatile frameworks that support this redesign are missing. Based on this, the present paper introduces such a framework and discusses the current state and comprehensiveness of its included metrics. An analysis of documents stemming from academic, practical and legal discourses was conducted in order to identify CE criteria and indicators, and consequently, these were synthesised in an integrated framework. The framework contains 29 categories, 73 criteria and 408 potential indicators assigned to the four dimensions: “Environmental”, “Economic”, “Social” and “Governance”. The integration of the different discourses enabled the development of a comprehensive set covering a wide range of metrics. Still, some important content gaps and methodological limitations have been identified that should be rectified to further refine the framework.